SCIENTIFIC AND THEORETICAL FOUNDATIONS FOR INCREASING THE EXPORT POTENTIAL OF AGRICULTURAL PRODUCTS - Mamatov, Akhmetjon Atajanovich; Khurramov, Azamat Fayzullaevich (THE INNOVATION ECONOMY, 2026)
The article examines the scientific and theoretical foundations, components, and factors of increasing the export potential of agricultural products, and develops proposals and recommendations for its improvement.